2005
DOI: 10.2169/internalmedicine.44.261
|View full text |Cite
|
Sign up to set email alerts
|

A Japanese Patient with Familial Mediterranean Fever Associated with Compound Heterozygosity for Pyrin Variant E148Q/M694I

Abstract: Familial Mediterranean fever (FMF) is an inherited inflammatory disease occurring mainly in Mediterranean and Middle Eastern populations. FMF is caused by mutations in the MEFV gene that encodes pyrin/marenostrin. Here, we report a Japanese female FMF patient with heterozygosity for the compound pyrin E148Q/M694I showing recurrent fever, serositis or delay in skin wound healing. Her father and elder sister were heterozygous for pyrin variant M694I alone and sometimes suffered from mild fever or delay in wound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 17 publications
1
19
0
Order By: Relevance
“…The E148Q mutation is considered to be the mildest mutation and to result in a milder form of FMF (19). It has also been reported that patients with homozygosity for the pyrin variant E148Q mutation have less severe symptoms and fewer attacks than those with heterozygosity for the pyrin variant E148Q/M694I mutation (15,16). The patient in the present case was found to have a heterozygous E148Q mutation.…”
Section: Discussionsupporting
confidence: 54%
“…The E148Q mutation is considered to be the mildest mutation and to result in a milder form of FMF (19). It has also been reported that patients with homozygosity for the pyrin variant E148Q mutation have less severe symptoms and fewer attacks than those with heterozygosity for the pyrin variant E148Q/M694I mutation (15,16). The patient in the present case was found to have a heterozygous E148Q mutation.…”
Section: Discussionsupporting
confidence: 54%
“…FMF is observed most frequently in Jewish, Armenian, Arab, Turkish, and Italian people, and it has been thought to be a rare disease in Japan. However, an increasing number of cases of FMF have been reported in Japan (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Unlike typical FMF cases in endemic areas, some cases in Japan have been sporadic and adult-onset cases.…”
Section: Introductionmentioning
confidence: 99%
“…In this issue, Nakamura et al report a 34-year-old Japanese female FMF patient with heterozygous E148Q/M694I mutation (15). Interestingly, E148Q heterozygous mutation seems to enhance the FMF clinical symptoms of M694I heterozygous phenotype in her pedigree analysis (15).…”
mentioning
confidence: 98%
“…Many other drugs for FMF, such as interferon alpha, thalidomide, reserpine, prazosin hydrochloride (20), and herbal medicine (19) have been reported to date (8). Because of the side effects, Nakamura et al tried to use azelastine, an anti-allergic drug in this patient rather than colchicine, and azelastine successfully reduced the frequency and degree of the attacks (15). As it is similar to colchicine in function in that it inhibits neutrophil chemotaxis and has less adverse effects, azelastine may be one of the promising drugs for FMF.…”
mentioning
confidence: 99%
See 1 more Smart Citation